Palatability status and animals preferences of forage plants in Koh Valley, Chitral, Hindu Kush Range Pakistan - Fazal, Zahid; Badshah, Lal (Ethnobotany Research and Applications, 2024)
Background: The different plants of the Koh area provide food and fodder to the cattle of the resident. The preferences of livestock and their nutritional requirements are quantified by the palatability of different plants. The current research work is the first attempt to document the palatability status of plant resources of Koh Valley. Objectives: The objective of this investigation was to assess the palatability of the flora and the preferences of grazing and browsing animals in the Koh valley Chitral, Khyber Pakhtunkhwa, Pakistan. Methods: Frequent field visits were carried out in order to gather information from local people and nomads of the research locality in different seasons. The palatability status of plant resources were also obtained through interviews, corner meeting, group discussion and visual observations about grazing animals. Results: The flora of the research area is freely grazed by goats, sheep and cows. Some 482 species of plants were assessed for its palatability classes during the survey. Out of them 140 plants assessed as rarely palatable followed by 115 mostly palatable, 91 highly palatable, 89 species less palatable and 47 were identified as non-palatable. On the basis of plant parts used, leaves top the list with 232 plants followed by whole plant having 193 plant species. Among cattle goats mostly utilized plants for grazing and browsing having 390 species followed by cows with 229 and sheep with 220 plant species. Conclusions: It was concluded that the research area had very rich palatable plants diversity. Different plant parts were consumed by livestock in Koh valley. Local inhabitants mostly depend on their cattle for survival. Several variables affect the palatability such as morphology, phenology and chemical nature of plants. Keywords: Palatability, grazing, browsing, Hindukush region, Koh valley.